The structure and function of rhizosphere bacterial communities: impact of chemical vs. bio-organic fertilizers on root disease, quality, and yield of Codonopsis pilosula - Huang, Bin; Chen, Yuxuan; Cao, Yi; Liu, Dongyang; Fang, Hua; Zhou, Changchun; Wang, Dong; Wang, Jie (Frontiers in Microbiology, 2024)
Long-term use of chemical fertilizer (CF) can cause soil compaction and acidification. In recent years, bio-organic fertilizer (BOF) has begun to replace CF in some vegetables and cash crops, but the application of CF or BOF has results in crop quality and disease occurrence. This study was to analyze the microbial mechanism of differences between CF and BOF in root disease, quality and yield of tuber Chinese herbal medicine. We studied the effects of CF, organic fertilizer, commercial BOF, biocontrol bacteria BOF and biocontrol fungi BOF on rhizosphere microbial community structure and function, root rot, quality and yield of Codonopsis pilosula at different periods after application, and analyzed the correlation. Compared with CF, the emergence rate and yield in BOF treatments were increased by 21.12% and 33.65%, respectively, and the ash content, water content, and disease index in BOF treatments were decreased by 17.87%, 8.19%, and 76.60%, respectively. The structural equation model showed that CF promoted the quality and yield of C. pilosula by influencing soil environmental factors, while BOFs directly drove soil bacterial community to reduce disease index and improve the quality and yield of C. pilosula. There was a stronger interaction and stability of soil microbial networks after BOF treatments. Microlunatus, Rubrobacter, Luteitalea, Nakamurella and Pedomicrobium were identified as effector-bacteria, which were related to disease prevention and yield and quality increase of C. pilosula. Microbial functional analysis indicated that the signal transduction and amino acid metabolism of soil bacteria might play a major role in improving the quality and yield of C. pilosula in the early and middle growth stages. In conclusion，compared with CF, BOFs obtained lower disease index of root rot and higher quality and yield of C. pilosula by changing the structure and function of rhizosphere bacterial community.